Analisis Kepribadian Muslim Terbaik pada Film Animasi I’m the Best Muslim - Hidayah, Raihan Rabbani; Rubino, Rubino; Lubis, Hasan Hamzah (TSAQOFAH, 2025)
Animated films as entertainment and educational media have strong potential in conveying moral messages and Islamic values. However, there are still few studies that specifically examine the representation of Muslim personality in animation media. This research aims to analyze the representation of the best Muslim personality in I'm The Best Muslim animation based on the perspective of Islamic psychology. This research uses descriptive qualitative method with content analysis approach. Data were collected from several episodes of the animation using an instrument in the form of a coding sheet prepared based on Muslim personality indicators according to Dr. Muhammad Uthman Najati, and validated by two experts (coders). The data analysis technique refers to the Miles, Huberman, and Saldana model, which includes the stages of data condensation, data presentation, and conclusion drawing. The results show that from a total of 19 statements of the best Muslim personality found, the worship aspect is the most dominant category (52.63%), followed by the community relations aspect (31.58%), emotional and compassion aspect (10.52%), and physical aspect (5.26%). The existence of this animation not only serves as a means of entertainment, but also contributes positively in shaping the ideal Muslim character, making it an alternative media in Islamic character education.